Reciprocal interaction between vascular filopodia and neural stem cells shapes neurogenesis in the ventral telencephalon - Di Marco, Barbara; Crouch, Elizabeth E.; Shah, Bhavin; Duman, Aset Ceren; Paredes, Mercedes F.; Ruiz de Almodóvar, Carmen; Huang, Eric J.; Alfonso, Julieta (Cell reports, 2020)
Angiogenesis and neurogenesis are tightly coupled during embryonic brain development. However, little is known about how these two processes interact. We show that nascent blood vessels actively contact dividing neural stem cells by endothelial filopodia in the ventricular zone (VZ) of the murine ventral telencephalon; this association is conserved in the human ventral VZ. Using mouse mutants with altered vascular filopodia density, we show that this interaction leads to prolonged cell cycle of apical neural progenitors (ANPs) and favors early neuronal differentiation. Interestingly, pharmacological experiments reveal that ANPs induce vascular filopodia formation by upregulating vascular endothelial growth factor (VEGF)-A in a cell-cycle-dependent manner. This mutual relationship between vascular filopodia and ANPs works as a self-regulatory system that senses ANP proliferation rates and rapidly adjusts neuronal production levels. Our findings indicate a function of vascular filopodia in fine-tuning neural stem cell behavior, which is the basis for proper brain development.
Gesehen am 30.11.2020